Effectiveness of Live Health Professional-Led Group eHealth Interventions for Adult Mental Health: Systematic Review of Randomized Controlled Trials - Cheryl L Currie; Richard Larouche; M Lauren Voss; Maegan Trottier; Rae Spiwak; Erin Higa; David R Scott; Treena Tallow (JMIR Publications, 2022)
BackgroundThe COVID-19 pandemic has had adverse impacts on mental health and substance use worldwide. Systematic reviews suggest eHealth interventions can be effective at addressing these problems. However, strong positive eHealth outcomes are often tied to the intensity of web-based therapist guidance, which has time and cost implications that can make the population scale-up of more effective interventions difficult. A way to offset cost while maintaining the intensity of therapist guidance is to offer eHealth programs to groups rather than more standard one-on-one formats. ObjectiveThis systematic review aims to assess experimental evidence for the effectiveness of live health professional-led group eHealth interventions on mental health, substance use, or bereavement among community-dwelling adults. Within the articles selected for our primary aim, we also seek to examine the impact of interventions that encourage physical activity compared with those that do not. MethodsOverall, 4 databases (MEDLINE, CINAHL, PsycINFO, and the Cochrane Library) were searched in July 2020. Eligible studies were randomized controlled trials (RCTs) of eHealth interventions led by health professionals and delivered entirely to adult groups by videoconference, teleconference, or webchat. Eligible studies reported mental health, substance use, or bereavement as primary outcomes. The results were examined by outcome, eHealth platform, and intervention length. Postintervention data were used to calculate effect size by study. The findings were summarized using the Synthesis Without Meta-Analysis guidelines. Risk of bias was assessed using the Cochrane Collaboration Tool. ResultsOf the 4099 identified studies, 21 (0.51%) RCTs representing 20 interventions met the inclusion criteria. These studies examined mental health outcomes among 2438 participants (sample size range: 47-361 participants per study) across 7 countries. When effect sizes were pooled, live health professional-led group eHealth interventions had a medium effect on reducing anxiety compared with inactive (Cohen d=0.57) or active control (Cohen d=0.48), a medium to small effect on reducing depression compared with inactive (Cohen d=0.61) or active control (Cohen d=0.21), and mixed effects on mental distress and coping. Interventions led by videoconference, and those that provided 8-12 hours of live health professional-led group contact had more robust effects on adult mental health. Risk of bias was high in 91% (19/21) of the studies. Heterogeneity across interventions was significant, resulting in low to very low quality of evidence. No eligible RCT was found that examined substance use, bereavement, or physical activity. ConclusionsLive eHealth group interventions led by health professionals can foster moderate improvements in anxiety and moderate to small improvements in depression among community-based adults, particularly those delivered by videoconference and those providing 8-12 hours of synchronous engagement. Trial RegistrationPROSPERO CRD42020187551; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=187551 International Registered Report Identifier (IRRID)RR2-10.1186/s13643-020-01479-3